Effect on nasopharyngeal pneumococcal carriage of replacing PCV7 with PCV13 in the Expanded Programme of Immunization in The Gambia - Roca, Anna (Vaccine, 2015)
INTRODUCTION: In 2011, two years after the introduction of 7-valent Pneumococcal conjugate vaccine (PCV7), the Gambian immunization programme replaced PVC7 with PCV13 (13-valent). Our objective was to assess the additional impact of PCV13 on prevalence of pneumococcal nasopharyngeal carriage. METHODS: We recruited healthy Gambian infants who had received three PCV doses. Nasopharyngeal swabs were collected from infants and their mothers during two cross-sectional surveys (CSS) conducted in infants vaccinated with PCV7 (CSS1) and vaccinated with PCV13 (CSS2). Pneumococci were isolated and serotyped following standardized methods. Whole genome sequencing was performed on non-typable pneumococcus isolated in CSS1 and CSS2. RESULTS: 339 and 350 infants and their mothers were recruited in CSS1 and CSS2, respectively. Overall prevalence of pneumococcal carriage was 85.4% in infants. Among infants, prevalence of vaccine type (VT) carriage was lower in CSS2 [9.4% versus 4.9% (p = 0.025) for PCV7-VT; 33.3% versus 18.3% (p < 0.001) for PCV13-VT and 23.9% versus 13.7% (p = 0.001) for the 6 additional serotypes included in PCV13]. At CSS2, there was a decrease of serotypes 6A (from 15.3% to 5.7%, p < 0.001) and 19F (from 5.6% to 1.7%, p = 0.007), and an increase of non-typable pneumococci (0.3–6.0%, p < 0.001), most of which (82.4%) were from typable serotype backgrounds that had lost the ability to express a capsule. Prevalence of overall and VT carriage in mothers was similar in CSS1 and CSS2. CONCLUSIONS: Replacing PCV7 for PCV13 rapidly decreased prevalence of VT carriage among vaccinated Gambian infants. An indirect effect in mothers was not observed yet. Vaccine-driven selection pressure may have been responsible for the increase of non-typable isolates.